Teaching Vocabulary to Young Learners through Snake and Ladder Game - Zikriyati Zikriyati; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
Vocabulary is one of the important elements in the process of learning, mastering, and using language. As a part of language elements, it should be taught earlier to the students in order to ease them in mastering a language in the future. However, teaching vocabulary to Young Learners is different from teaching vocabulary to teenagers and adults for some reasons. Generally, young learners are children who are still in a period of good growth. They tend to be more active because they like playing and doing many activities. They cannot listen longer and cannot handle more abstract ideas but may be willing to speak, sing, or move. For those reasons, teachers have to create a learning situation based on students’ need and interest which is learning by playing. This paper will present an interesting activity named “Snake and Ladder” game that can be used as a solution in teaching vocabulary to young learners. Through the implementation of